2022
DOI: 10.1002/marc.202100678
|View full text |Cite
|
Sign up to set email alerts
|

Zwitterionic Ammonium Sulfonate Polymers: Synthesis and Properties in Fluids

Abstract: This article is dedicated to Rudolf Zentel in honor of his significant contributions to the fields of polymer chemistry, nanoscience, and polymeric biomaterials, as well as his promotion of international scientific collaboration and student exchange.Polymer zwitterions continue to emerge as useful materials for numerous applications, ranging from hydrophilic and antifouling coatings to electronic materials interfaces. While several polymer zwitterion compositions are now well established, interest in this fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…In terms of polymerization, high-molecular-weight polymers have been obtained by general radical polymerization and living polymerization, and have been copolymerized with various monomers. [136][137][138][139] Research on biointerfaces based on these polymers is progressing; the results have shown promise in terms of expressing new functions.…”
Section: Construction Of Biointerfacesmentioning
confidence: 99%
“…In terms of polymerization, high-molecular-weight polymers have been obtained by general radical polymerization and living polymerization, and have been copolymerized with various monomers. [136][137][138][139] Research on biointerfaces based on these polymers is progressing; the results have shown promise in terms of expressing new functions.…”
Section: Construction Of Biointerfacesmentioning
confidence: 99%
“…To prepare antifouling surfaces, methacrylate and acrylamide are the most common polymerizable groups used for zwitterionic monomers [2,3]. However, some studies reported the use of a styrenic polymerizable group [6,7]. Very recently, T. Emrick et al…”
Section: Introductionmentioning
confidence: 99%
“…described the preparation of new zwitterionic monomers using 4-vinylbenzyl sultone as precursor to ammonium sulfonate monomers [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies reported the Molbank 2022, 2022, M1414. https://doi.org/10.3390/M1414 https://www.mdpi.com/journal/molbank use of a styrenic polymerizable group [6,7]. Very recently, T. Emrick et al, described the preparation of new zwitterionic monomers using 4-vinylbenzyl sultone as a precursor to incorporating ammonium sulfonate units [6].…”
Section: Introductionmentioning
confidence: 99%
“…https://doi.org/10.3390/M1414 https://www.mdpi.com/journal/molbank use of a styrenic polymerizable group [6,7]. Very recently, T. Emrick et al, described the preparation of new zwitterionic monomers using 4-vinylbenzyl sultone as a precursor to incorporating ammonium sulfonate units [6]. Indeed, numerous studies reported in the literature have shown that excellent antibacterial and anti-fouling properties were achieved by combination of ammonium cationic parts with sulfonate anionic moiety [8,9].…”
Section: Introductionmentioning
confidence: 99%